2015
DOI: 10.1128/jcm.01631-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Carba NP, Modified Carba NP, and Updated Rosco Neo-Rapid Carb Kit Tests for Carbapenemase Detection

Abstract: The accurate detection of carbapenemase-producing organisms is a major challenge for clinical laboratories. The Carba NP test is highly accurate but inconvenient, as it requires frequent preparation of fresh imipenem solution. The current study was designed to compare the Carba NP test to two alternative tests for accuracy and convenience. These were a modified Carba NP test that utilized intravenous (i.v.) imipenem-cilastatin, which is less expensive than reference standard imipenem powder, and an updated ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 17 publications
0
16
2
Order By: Relevance
“…On the other hand, the calculated analytical performances of RCNP and NRCK were lower than previously reported (9,11,14,16). At least two reasons might have accounted for those differences.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…On the other hand, the calculated analytical performances of RCNP and NRCK were lower than previously reported (9,11,14,16). At least two reasons might have accounted for those differences.…”
Section: Discussioncontrasting
confidence: 46%
“…However, this high proportion of OXA-48 producers is in line with the current epidemiology of CPE observed in several European countries such as Belgium, France, Spain, or Germany (4). In comparison with this report, OXA-48 producers represented only 7.9% to 27.5% of the screened CPE isolates in other studies where better overall tests performances were reported (11,13,14,16).…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…In principle, the test is similar to the classic ␤-lactamase detection assays described by Escamilla and by Skinner and Wise in the 1970s, in which benzylpenicillin acidimetrically produced a red color after hydrolysis by Haemophilus influenzae ␤-lactamase (1, 2). With the Carba NP test, hydrolysis of imipenem produces acid and drives the pH indicator, phenol red, from red to yellow.The Carba NP test has been studied by several investigators (3-14), including evaluations and comparisons to a commercial version (15)(16)(17)(18)(19)(20). However, the literature lacks consistency in the Carba NP methodology.…”
mentioning
confidence: 99%
“…The Carba NP test has been studied by several investigators (3-14), including evaluations and comparisons to a commercial version (15)(16)(17)(18)(19)(20). However, the literature lacks consistency in the Carba NP methodology.…”
mentioning
confidence: 99%